Exploratory study on the occurrence and dynamics of yeast-mediated nicotinamide riboside production in craft beers. (July 2021) - Garofalo, Cristiana; Sabbatini, Riccardo; Zamporlini, Federica; Minazzato, Gabriele; Ferrocino, Ilario; Aquilanti, Lucia; Raffaelli, Nadia; Osimani, Andrea
Abstract: In this study, nicotinamide riboside (NR), a form of vitamin B3, and its precursors nicotinamide mononucleotide (NMN) and NAD + were quantitated by a fluorometric assay in ten commercial craft beers and throughout the fermentation process of a laboratory-scale beer. All tested beers from different commercial Saccharomyces cerevisiae strains contained NAD + (ranging from 1.10 μM to 17.80 μM). NR concentrations ranged from 0.48 to 3.25 μM, while the content of NMN was approximately 0.9 μM. NR and NMN were only present in beers produced with S . cerevisiae strain US-05. Data from laboratory-scale beer productions using S. cerevisiae strain US-05 showed that the addition of hops [amarillo (alpha acid: 9.0%) (4 g/L) and centennial (alpha acid: 8.5%) (4 g/L) varieties] at the 9th day of fermentation significantly increased NR production up to 6.11 μM at the end of a typical fermentation of 21 days, and up to 11.42 μM at 45 days of fermentation. The rapid increase in NR formation only occurred if both hops and yeast were present, and the burst was also confirmed in fermentations trials performed with S. cerevisiae strain CBS1171 T and by replacing wort with YPD medium. This study can serve as baseline for further research on yeast-hop interaction. Highlights: The presence of NR, NMN and NAD + in craft beers was assessed. The presence of the three vitamers in beers is S. cerevisiae strain-dependent. Hop addition during the beer fermentation increases NR levels. The boosting effect of hop is wort-independent. An experimental model to study the hop-yeast interaction is provided.